Magnetic field amplification in FR II radio sources - De Young, D (2002)
If magnetic fields are near the energy equipartition value in the lobes of FR II radio sources, it can be shown that it is very unlikely that such fields are passively advected outward with the jet that creates the source. This has led to the idea that the fields are amplified within the lobes; and a likely site for this is the complex and turbulent region inside the hot-spots, as suggested by Blundell, Rawlings and Willott (1999). if this process occurs, a natural question is the subsequent evolution of the field strength and geometry as the field and fluid leave the hot-spot and fill the lobe. This evolution is followed via a time dependent turbulent MHD calculation under a variety of conditions. While the small scale field can decay away rather quickly, the large scale field structures remain surprisingly robust.